2001
DOI: 10.1300/j010v32n04_05
|View full text |Cite
|
Sign up to set email alerts
|

Experience and Covariates of Depressive Symptoms Among a Cohort of HIV Infected Women

Abstract: The scores on the CESD were elevated for both HIV positive and HIV negative women and the differences between the groups were small. Lower socioeconomic status and social support and higher substance use and domestic abuse were associated with depressive symptoms similarly for both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
47
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 31 publications
8
47
0
Order By: Relevance
“…[28][29][30][31][32][34][35][36][51][52][53][54][55][56][57][58][59][60][61] Significantly higher percentages of women who were HIV-positive, had experienced IPV in the past year, and had used hard drugs in the past 30 days exhibited higher depressive symptoms, without adjusting for sociodemographic factors. However, when adjusting for the other SAVA factors, sociodemographic factors, social support and alcohol abuse, only the experience of IPV in the past year and drug use in the past 30 days remained significant, as did reporting low social support.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31][32][34][35][36][51][52][53][54][55][56][57][58][59][60][61] Significantly higher percentages of women who were HIV-positive, had experienced IPV in the past year, and had used hard drugs in the past 30 days exhibited higher depressive symptoms, without adjusting for sociodemographic factors. However, when adjusting for the other SAVA factors, sociodemographic factors, social support and alcohol abuse, only the experience of IPV in the past year and drug use in the past 30 days remained significant, as did reporting low social support.…”
Section: Discussionmentioning
confidence: 99%
“…Depression was assessed using a score derived from the Center for Epidemiologic Study of Depression (CES-D) symptom checklist, where depressive symptoms and the likelihood of clinical depression were indicated by a score of 16 or higher 34 as validated by other studies in this population. 35 Current drug use pattern was examined as none, only marijuana use, or hard drug use, which included any injection drug use, heroin, cocaine, crack, or methadone amphetamine use. Other variables evaluated for all women included current alcohol use, which was examined as abstain-light (0-2 drinks per week) versus moderate-heavy drinking (!3 drinks per week), current and former smoking, current hormonal contraception use, current or prior cancer, and hepatitis C infection (HCV) status.…”
Section: Wihs Is An Ongoingmentioning
confidence: 99%
“…The HIV Epidemiology Research Study (N = 765; Ickovics et al, 2001) found that 77% of HIV-infected women reported intermittent or chronically high levels of depressive symptoms over time. In addition, the Women's Interagency HIV Study (N = 1993;Richardson et al, 2001) identified 58% of HIV-infected women as probable cases of clinical depression (e.g., CES-D scores ≥ 16). Smaller studies have documented a similar prevalence (56 -61%) depressive symptoms (e.g., Catz, Gore-Felton, & McClure, 2002;Siegel, Karus, Raveis, & Hagen, 1998;Simoni & Cooperman, 2000;Updegraff, Taylor, Kemeny, & Wyatt, 2002).…”
Section: Introductionmentioning
confidence: 99%